Desarrollo de la marca turística del cantón Bolívar provincia de Manabí - Mora Faubla, María Alejandra (2012)
This job was to study the canton Bolivar, which was designed for promoting tourism brand. Visits were made to observe, analyze and diagnose the current situation which is the area involved and the determination of potential for tourism. Surveys were prepared for the people of Bolivar country, we interviewed those responsible for tourism in the county and several graphic designers to start developing the process of branding. It was concluded that the county has great potential Bolivar tourist offer, which was developed for the design of the tourism brand and its respective manual in order to improve the promotion and tourism development in the county and he is sworn in and elected a tourist destination to be visited.